The Role of Social-Commerce, Influencers, and Diderot Effect on Consumers’ Impulsive Buying: A Systematic Review - Iwan Sukmana; Ibnu Aditya Karana; Wilfried Agusman; Intan Wahyuningtias; Lela Nurlaela Wati (International Journal of Entrepreneurship, Business, and Creative Economy, 2026)
The increasingly intensive integration of social media and digital commerce has transformed impulsive buying from an individual behavior into a phenomenon structurally embedded within the digital consumption ecosystem. This systematic literature review aims to synthesize theoretical and empirical evidence on the roles of social commerce, influencer-driven persuasion, and the Diderot Effect in shaping impulsive buying in contemporary digital markets. The study applies the PRISMA method by examining 26 reputable Scopus-indexed journal articles published between 2021 and 2026. Articles were selected through a multi-stage screening process based on inclusion criteria, methodological quality, thematic relevance, and subsequently analyzed using a thematic synthesis approach. The review findings indicate that impulsive buying is a socio-technical outcome simultaneously produced by algorithmic design, social interaction, and post-purchase consumption dynamics. Social commerce features such as live streaming, short-form videos, social proof cues, and in-app purchasing mechanisms function as primary stimuli that intensify emotional arousal, hedonic pleasure, and fear of missing out. Influencers further amplify these effects through perceived credibility, parasocial relationships, and identity-based narratives. Moreover, the Diderot Effect is identified as a key explanatory mechanism linking initial impulsive purchases to sequential and excessive consumption. This review identifies theoretical gaps, methodological limitations, and ethical concerns, and proposes a future research agenda that emphasizes integrative models, longitudinal designs, and responsible social commerce governance.